Pelatihan Penerapan Kontrak Bisnis Syariah Dalam Pengelolaan Ziswaf Di Pesantren Darul Mukhlisin Cempedak Lobang Serdang Bedagai Sumut - Muhammad Zuhirsyan; Supaino; Diena Fadhilah; Nurlinda (Jurnal Tiyasadarma, 2025)
Islamic boarding schools (pesantren) can strive to implement Sharia-based economic practices in their various economic activities. These Sharia-based economic practices have not yet been fully explored and implemented by Islamic boarding schools, given their various limitations, including human resources and materials. However, at least these practices can be gradually implemented. As Islamic educational institutions, Islamic boarding schools are suitable and appropriate places for the implementation and even study of Sharia economics. The purpose of implementing this community service is so that partners, in this case the administrators of the Darul Mukhlisin Islamic Boarding School, receive education regarding the management of Zakat, Infak, Sedekah and Waqf (ZISWAF) based on sharia business contracts from the team and then can disseminate it to various parties involved in the management of ZISWAF in the Islamic boarding school. The activity will be held at the Darul Mukhlisin Islamic Boarding School, Cempedak Lobang Serdang Bedagai, North Sumatra. During the implementation, participants consisting of caretakers and final grade VI KMI (XII MAS) students were given training on sharia-based business management. Then, it was continued with briefings on sharia business contracts and intra-pesantren ZISWAF management. The training activities will be made as interesting as possible, fun learning, and in addition to learning they will also be given motivation. In this training at the Islamic Boarding School, participants were presented with various knowledge about sharia business and ZISWAF. The team also provided various motivations to participate in implementing sharia business in Islamic boarding schools while also helping to provide assistance in the form of a printer that will later help pioneer and improve ZISWAF management at this educational institution. The problem of limited understanding of sharia business contracts can be overcome by providing training on sharia business contracts, so that partners can understand them well. Partners receive education on ZISWAF management.